(untitled) (Bangladesh Journal of Botany, 2015)
Nine new cytoplasmic male sterile (CMS) analogues on the basis of different CMS sources were developed and evaluated for morphophysiological, yield and biochemical traits. Analysis of variance indicated significant differences between CMS analogues for all the traits. The genetic components analysis indicated that selection for grain yield accompanied with high harvest index, large head size and biological yield can be effectively used for genetic improvement in sunflower. D2analysis revealed sufficient diversity between CMS analogues which can be exploited for developing hybrids based on different cytoplasmic sources. Intra-cluster distance of 72.5 observed for the analogues present in cluster I (E002-91A, ARG-2A, DV-10A and PRUN-29A) revealed cytoplasmic dissimilarity between these sources. CMS ARG-3A was the most diverse CMS lines among all. As a result of this study the most prospective CMS analogues were designated for future use in hybrid breeding programme. The CMS analogues PRUN 29A and ARG 3 may be effectively used for developing high seed and oil yielding hybrids with desirable fatty acid composition. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22719 Bangladesh J. Bot. 44(1): 23-30, 2015 (March)